Effect of Antirotational Two-Piece Titanium Base on the Vertical Misfit, Fatigue Behavior, Stress Concentration, and Fracture Load of Implant-Supported Zirconia Crowns - Adolfi, Dario [UNESP]; Grangeiro, Manassés Tercio Vieira [UNESP]; Ausiello, Pietro; Bottino, Marco Antonio [UNESP]; Tribst, João Paulo Mendes (MDPI, 2023)
This study investigated the effects of antirotational titanium bases on the mechanical behavior of CAD/CAM titanium bases used for implant-supported prostheses. The aim was to assess the impact on the marginal fit, fatigue behavior, stress concentration, and fracture load of implant-supported CAD/CAM zirconia crowns. Forty titanium implants were divided into two groups: those with antirotational titanium bases (ARs) and those with rotational titanium bases (RTs). Torque loosening and vertical misfit were evaluated before and after cyclic fatigue testing (200 N, 2 Hz, 2 × 106 cycles). Fracture resistance was assessed using a universal testing machine (1 mm/min, 1000 kgf), and failed specimens were examined with microscopy. Three-dimensional models were created, and FEA was used to calculate stress. Statistical analysis was performed on the in vitro test data using two-way analysis of variance and Tukey’s test (α = 0.5). Results show that the presence of an antirotational feature between the implant and titanium base reduced preload loss and stress concentration compared to rotational titanium bases. However, there were no differences in vertical misfit and resistance to compressive load.
Keywords: dental implant abutment design; dental implants; fatigue; finite element analysis; zirconia